2016
DOI: 10.1121/1.4971423
|View full text |Cite
|
Sign up to set email alerts
|

Optimized single-number quantity for rating the airborne sound insulation of constructions: Living sounds

Abstract: ISO 717-1 [(1996). International Organization for Standardization, Geneva, Switzerland] and ASTM 413 [(2010). American Society for Testing and Materials International] define various single-number quantities (SNQs) that are commonly used to rate objectively airborne sound insulation of constructions. Recent psychoacoustic evidence suggests that none of them is appropriate for a wide range of living sound stimuli. The purpose of the study was to develop an alternative compromising SNQ for the frequency range 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 11 publications
0
36
0
9
Order By: Relevance
“…Furthermore, the different types of sound stimuli are highlighted as an important parameter in some studies 10,13 because speech sounds have more high-frequency content while low frequencies are dominant in music sound stimuli. There are variations of course, for the cases of different sounds tested and responses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the different types of sound stimuli are highlighted as an important parameter in some studies 10,13 because speech sounds have more high-frequency content while low frequencies are dominant in music sound stimuli. There are variations of course, for the cases of different sounds tested and responses.…”
Section: Discussionmentioning
confidence: 99%
“…This review demonstrates that different descriptors work better for various stimuli. However, in Virjonen et al 13 and Rasmussen and Rindel, 14 a spectrum adaptation term is suggested to formulate the measure: R C w opt + which predicts well most airborne sound types (except baby cry) within the full measurement spectrum of 50-5000 Hz and it is different to the standardized adaptation term C 50 5000 − . In some cases, the study design parameters are problematic: the sample size of listening tests can be small as in Pedersen et al 7 and Vian et al 8 or extremely small as in literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations